2009
DOI: 10.1007/s11665-009-9351-8
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Behaviour of Nickel-Titanium Laser Welded Joints

Abstract: In this study, the effects of Nd:YAG laser welding on the fracture behavior of Ni-rich nickel-titanium sheets are analyzed by experimental investigations. The welding was carried out in open air conditions by using a special shielding/clamping system to avoid the chemical contamination of the molten zone and the formation of hot cracks. Mechanical tests of standard dog bone-shaped and single edge crack specimens were carried out to measure the stress-strain response and the fracture resistance of both the base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…While similar welds NiTi/NiTi are well succeeded, joining these materials to others is not a simple issue, due to hightemperature diffusion with localized changes in chemical composition and the formation of brittle intermetallics [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While similar welds NiTi/NiTi are well succeeded, joining these materials to others is not a simple issue, due to hightemperature diffusion with localized changes in chemical composition and the formation of brittle intermetallics [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Embrittlement occurs mainly due to high-temperature reaction of elements such as oxygen, nitrogen, and hydrogen. Brittle intermetallics like Ti 2 Ni and Ti 3 Ni can precipitate during solidification, having adverse effects on strength and shape memory characteristics [12,14]. This work aimed to analyze the possibility of welding NiTi to Ti-6Al-4V plates by laser in butt joint configuration.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of hybrid welding arise due to synergy effect and interaction between two heat sources, i.e., laser and arc [1,7,3]. During laser and hybrid welding, a deep and narrow vapor filled cavity is created, the so-called keyhole, due to high-focused laser energy and thus allows for a much deeper weld penetration to be obtained [8,3,[9][10][11]. Metal vapors leaving the laser-generated keyhole are the main source of this laser-arc synergy when the arc and laser are in close proximity [3,5,1].…”
Section: Introductionmentioning
confidence: 99%
“…Gugel et al [10] reported, for laser welded Ni-rich wires, a tensile strength up to 75% of the base material, as well as a pronounced SE up to 10 cycles. Maletta et al [11] evaluated the fracture behaviour of laser welded NiTi and reported very interesting results regarding tensile strength of welded joints. As a continuation of a previous study [9], Khan et al [12] analyzed the effects of laser processing on the transformation temperatures of Nitinol; their DSC results revealed additional high temperature transformation peaks that can be attributed to the local phase conversion induced by laser processing; these results were further corroborated with RT XRD analysis, showing only austenite in the base metal and added martensite peaks in the melted metal.…”
Section: Introductionmentioning
confidence: 99%